Validity of Student Worksheets Based on Multiple Representations of Electrolyte and Non-Electrolyte Solution Materials - Nazwa Syauqiah; Helda Rahmawati; Ratna Kartika Irawati (Journal of Mathematics Science and Computer Education, 2024)
Multiple representations can facilitate the understanding of abstract chemical concepts. Multiple representations can be incorporated into teaching materials, such as Student Worksheets, to create Multiple Representation-based Student Worksheets. This study aims to analyze the validity of Student Worksheets based on multiple representations of electrolyte and non-electrolyte solutions. The research utilized the Research and Development (R&D) model with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development stages, reaching the development stage in this study. Data were obtained from material expert and media expert validators. Descriptive statistical analysis was used to analyze the validity results. The Student Worksheets based on multiple representations of electrolyte and non-electrolyte solution materials achieved an average validity percentage of 84.37% from material experts and 95% from media experts, categorizing them as very valid. These worksheets, focusing on the validity aspect, are effective in assisting students in understanding chemical concepts.